2010
DOI: 10.1063/1.3452358
|View full text |Cite
|
Sign up to set email alerts
|

LuAG:Ce fibers for high energy calorimetry

Abstract: The main objective of this contribution is to point out the potentialities of cerium doped LuAG single crystal as pixels and fibers. We first show that after optimization of growth conditions using Bridgman technology, this composition exhibits very good performances for scintillating applications (up to 26 000 photons/MeV). When grown with the micropulling down technology, fiber shapes can be obtained while the intrinsic performances are preserved. For the future high energy experiments requiring new detector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
57
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(67 citation statements)
references
References 26 publications
2
57
1
1
Order By: Relevance
“…The present studies were initiated by the needs of development and optimization of LuAG:Ce fibers for high energy calorimetry [10,11]. In this application crystalline fibers are required with good scintillation parameters in terms of luminosity and decay time; these parameters are in many cases dependent on crystal composition, more especially the activator concentration, as it is the case for some other scintillators, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The present studies were initiated by the needs of development and optimization of LuAG:Ce fibers for high energy calorimetry [10,11]. In this application crystalline fibers are required with good scintillation parameters in terms of luminosity and decay time; these parameters are in many cases dependent on crystal composition, more especially the activator concentration, as it is the case for some other scintillators, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9,10 ] It was found that LuAG:Ce single crystal containing 0.55 at% Ce 3+ ions prepared by Bridgman technique is a highly competitive scintillator displaying a LY of about 26000 photons/MeV with a shaping time of 1.5 μs, close to that of Lu 2 SiO 5 :Ce (LSO:Ce). [ 11 ] Based on the understanding of defect chemistry, an effective bandgap engineering approach was successfully applied to the LuAG system. Multicomponent garnets, featuring a balanced admixture of Gd and Ga cations in the Lubased garnet structure, form a new family of materials with an amazingly high light yield up to 58000 photons/MeV, a value exceeding that of the best Lu 2-x Y x SiO 5 :Ce (LYSO:Ce) materials by about 40%.…”
mentioning
confidence: 99%
“…Cerium-doped crystals with the garnet structure have a high potential for applications as high-performance scintillators [1][2][3]. They are also widely used in white LEDs [4] and considered as a promising material for quantum storage of optical information [5,6].…”
Section: Introductionmentioning
confidence: 99%